Interfacial polymerization of conductive polymers: Generation of polymeric nanostructures in a 2-D space - Dallas, P; Georgakilas, P (Elsevier, 2015)
In the recent advances in the field of conductive polymers, the fibrillar or needle shaped nanostructures of polyaniline and polypyrrole have attracted significant attention due to the potential advantages of organic conductors that exhibit low-dimensionality, uniform size distribution, high crystallinity and improved physical properties compared to their bulk or spherically shaped counterparts. Carrying the polymerization reaction in a restricted two dimensional space, instead of the three dimensional space of the one phase solution is an efficient method for the synthesis of polymeric nanostructures with narrow size distribution and small diameter. Ultra-thin nanowires and nanofibers, single crystal nanoneedles, nanocomposites with noble metals or carbon nanotubes and layered materials can be efficiently synthesized with high yield and display superior performance in sensors and energy storage applications. In this critical review we will focus not only on the interfacial polymerization methods that leads to polymeric nanostructures and composites and their properties, but also on the mechanism and the physico-chemical processes that govern the diffusion and reactivity of molecules and nanomaterials at an interface. Recent advances for the synthesis of conductive polymer composites with an interfacial method for energy storage applications and future perspectives are presented.